Preoperative Marking Using Endobronchial Ultrasonography with a Guide-sheath for a Small Pulmonary Nodule: a Case Report - Tsuboi, Mitsuhiro; Imakura, Takeshi; Mori, Ayaka; Inayama, Mami; Miyamoto, Kenya; Matsumoto, Daisuke; Hirose, Toshiyuki; Kakiuchi, Souji; Bandou, Noriko; Haku, Takashi (The Journal of the Japan Society for Respiratory Endoscopy, 2022)
Background. Various marking techniques for the identification of small impalpable lung nodules have been reported. Case. A 72-year-old man who had undergone surgery for bladder and rectal cancer presented with a solitary small lung tumor located in the right S3 on chest computed tomography (CT). Due to tumor enlargement, it was suspected to be metastatic; thus, surgery was performed. Because the tumor was located near the B3bi, we performed presurgical coil marking using an endobronchial ultrasonography with a guide-sheath. During surgery, we identified the marking coil using X-ray fluoroscopy and subsequently resected the target tumor and marking coil. Conclusion. This method was safe and useful for marking small impalpable lung nodules.